2019
DOI: 10.1029/2018gl081789
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Crustal Seismicity in San‐in District, Southwest Japan

Abstract: A growing body of evidence suggests that seismicity is seasonally modulated in a variety of tectonic environments. Identifying cyclic variations in seismicity improves our understanding of the physics of earthquake triggering. We explored seasonal modulation of crustal seismicity in San‐in district, southwest Japan, using a new method that adopts uncertainties derived from a probability‐based declustering procedure. We determined that semiannual variation in background seismicity rate, which increases in sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…A similar pore pressure and seismic velocity variation also occurs at other locations across Chugoku and Shikoku (Fig S3). It is known that rainfall in July-September can trigger seasonal seismicity in the Chugoku area (Ueda et al 2019). The similar timeline suggests that the longer period seismic velocity change might have been 20 influenced by pore pressure change induced by rainfall, although the long period variation is also influenced by sea level and atmospheric pressure variations.…”
Section: Seismic Velocity Changes Due To Pore Pressure Diffusionmentioning
confidence: 72%
“…A similar pore pressure and seismic velocity variation also occurs at other locations across Chugoku and Shikoku (Fig S3). It is known that rainfall in July-September can trigger seasonal seismicity in the Chugoku area (Ueda et al 2019). The similar timeline suggests that the longer period seismic velocity change might have been 20 influenced by pore pressure change induced by rainfall, although the long period variation is also influenced by sea level and atmospheric pressure variations.…”
Section: Seismic Velocity Changes Due To Pore Pressure Diffusionmentioning
confidence: 72%
“…A similar pore pressure and seismic velocity variation also occurs at other locations across Chugoku and Shikoku (Additional file 1: Figure S3). It is known that rainfall in July-September can trigger seasonal seismicity in the Chugoku area (Ueda and Kato 2019). The similar timeline suggests that the longer period seismic velocity change might have been influenced by pore pressure change induced by rainfall, although the long period variation is also influenced by sea level and atmospheric pressure variations.…”
Section: Seismic Velocity Changes Due To Pore Pressure Diffusionmentioning
confidence: 73%
“…Although earthquakes are often weakly correlated to tides, tectonic tremors seem strongly correlated to tides both in the roots of strike-slip faults (Thomas et al, 2009(Thomas et al, , 2012 and subduction zones (Houston, 2015;Rubinstein et al, 2008;Yabe et al, 2015) where slow slip also is modulated by tidal stresses (Hawthorne & Rubin, 2010). Seasonal variation of seismicity driven by surface load variations has been reported in several studies (e.g., Amos et al, 2014;Bettinelli et al, 2008;Ueda & Kato, 2019). However, in most places, the seismicity rate depends weakly on tides (Cochran et al, 2004;Tanaka et al, 2002), except at mid-ocean ridges (e.g., Tolstoy et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
“…It has also been observed that slow slip can be modulated by tidal stresses (Hawthorne & Rubin, 2010). Seasonal variation of seismicity driven by surface load variations have been reported in several studies (e.g., Bettinelli et al, 2008;Amos et al, 2014;Ueda & Kato, 2019). However, in most places, the seismicity rate depends weakly on tides (Tanaka et al, 2002;Cochran et al, 2004), except at mid-ocean ridges, where a particularly strong response has been observed (e.g., Tolstoy et al, 2002).…”
Section: Introductionmentioning
confidence: 93%